The Effect of Vitamin D Administration on Glycemic Control in Patients with Type 2 Diabetes Mellitus : A Systematic Review - Fahmi Iskandar Aminullah; Jazilatul Hikmia (The International Journal of Medical Science and Health Research, 2026)
Introduction: Vitamin D deficiency is highly prevalent among patients with type 2 diabetes mellitus (T2DM) and has been linked to impaired insulin secretion and insulin resistance. However, the effects of vitamin D supplementation on glycemic control remain controversial. Methods: This systematic review synthesized evidence from 80 randomized controlled trials, etc identified through structured screening. Studies enrolling adults with T2DM receiving vitamin D supplementation (cholecalciferol, ergocalciferol, calcitriol, or analogs) with a control group and reporting glycemic outcomes (HbA1c, fasting glucose, HOMA-IR) were included. Results:  HbA1c (WMD −0.20% to −0.32%), fasting plasma glucose (WMD −5.02 mg/dL), and HOMA-IR (WMD −0.42 to −0.66). However, effects were highly heterogeneous. Positive outcomes were predominantly observed in vitamin D‑deficient (25(OH)D <30 nmol/L), poorly controlled (HbA1c >8%), non‑obese patients, particularly in Middle Eastern and South Asian populations. Null results consistently emerged from well‑controlled European/American cohorts with baseline 25(OH)D near sufficiency. Effect modifiers included baseline vitamin D status, obesity, intervention duration (short‑term >12 weeks showed benefit; long‑term did not), dose (>2,000 IU/day more effective), and co‑supplementation with calcium. Safety was excellent, with no clinically significant hypercalcemia. Discussion: The apparent contradiction between positive meta-analyses and null individual trials is resolved by recognizing that benefits are restricted to specific subpopulations. Vitamin D supplementation likely improves glycemic control through enhanced insulin secretion and insulin sensitivity, but only when baseline deficiency is corrected and patients have sufficient glycemic headroom for improvement. Obese patients require higher doses due to adipose sequestration. Conclusion: Vitamin D supplementation produces small but real improvements in glycemic control in T2DM patients who are vitamin D deficient, poorly controlled, and non‑obese, or who receive dose‑adjusted high‑dose therapy. Routine supplementation is not recommended for vitamin D‑replete or well‑controlled patients. Future trials should focus on personalized dosing based on baseline 25(OH)D, BMI, and HbA1c.